Unlocking Imagination through Living Books: A Case Study on Deep Literacy Engagement in Early Childhood within a Charlotte Mason Community in Indonesia - Noviana Mustapa; Erie Siti Syarah; Erna Risnawati; Muktia Pramitasari; Siti Kholijah Kassim (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study examines the perceptions of parents adhering to the Charlotte Mason educational philosophy regarding the use of living books in fostering literacy engagement among children. A total of 119 parents participated in this study, selected through purposive sampling based on specific inclusion criteria: their active practice of the Charlotte Mason method and experience in reading living books aloud to their children. The participants predominantly comprised mothers (79.8%), aged between 21 and 50 years, and were predominantly residing in urban areas throughout Indonesia. Employing a quantitative descriptive research design, data were collected through a self-constructed questionnaire consisting of 38 items categorized into four dimensions: perceptions of the benefits of reading living books aloud, reasons for encouraging children to retell stories, rationale for selecting living books, and methods of reading living books. The questionnaire was distributed via Google Forms, and the collected data were analyzed using descriptive statistics with SPSS version 26. The results indicated that respondents possessed highly positive perceptions regarding the cognitive, emotional, and social benefits of reading living books aloud to children. Additionally, parents perceived the practice of asking children to retell stories as beneficial for enhancing language skills, self-confidence, and narrative abilities. The study revealed that living books play a significant role in fostering deep literacy engagement and socio-emotional development in early childhood. The findings provide significant insights for educators, parents, and policymakers in designing effective literacy programs that integrate living books as an essential pedagogical tool and resources.